Innovation leadership in practice : how leaders turn ideas into value in a changing world - Jensen, Karina R.; Kaudela-Baum, Stephanie; Sheffield, Rob (Emerald Publishing Limited, 2023)
Innovation leadership is essential to survive in today's turbulent landscape. For many organisations, their environment is characterized by internationalization, customer centricity, digitalization, sustainability, and a call for greater diversity. In these volatile, uncertain, ambiguous, and complex (VUCA) settings, there is also the need to create new and sustainable sources of value. How are current-day leaders helping to turn ideas into value, whether that be through new products, services, markets, experiences, partnerships, processes, or business models? What are the new competencies and skills required in order to respond and effectively innovate in a changing environment? Innovation Leadership in Practice provides a unique source of new insights on the role of innovation leadership and effective practices through conceptual models, empirical case studies, development interventions, and tools.
Includes index.
Keywords: Leadership.; Business & Economics -- Leadership.; Management: leadership & motivation.; elektronické knihy; electronic books